Talking to Patients 900 - 张学智 王学美 叶晖 (中国结合医学杂志：英文版, 2016)
Co-authored by XIE Fang and XIE Zhu-fan and published by China＇s Foreign Languages Press in April 2016,Talking to Patients 900 is China＇s first bilingual reference brochure of medical history for Chinese medicine（CM）professionals.Currently an emeritus professor of CM and integrative medicine at Peking University＇s First Medical School,